2003
DOI: 10.1097/01.mp.0000097367.56816.5e
|View full text |Cite
|
Sign up to set email alerts
|

Potential Role of Bcl-2 and Bax mRNA and Protein Expression in Chronic Hepatitis Type B and C: A Clinicopathologic Study

Abstract: Bcl-2 oncoprotein regulates programmed cell death by providing a survival advantage to rapidly proliferating cells, and bax protein promotes apoptosis by enchanting cell susceptibility to apoptotic stimuli. In this study, we assessed the expression of bcl-2 and bax in liver biopsies from patients with chronic hepatitis (CH) Type B (HBV) and C (HCV). The study comprised 65 liver biopsies from 65 patients with HBV (n = 37) and HCV (n = 28) and 10 normal liver biopsies as controls. The HAI score ranged from 3/18-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 28 publications
3
18
0
Order By: Relevance
“…The mitochondrial outer membrane integrity is maintained by Bcl-2, while increased membrane permeability by Bax releases apoptogenic factors in the cytosol, which activate caspase-9 and caspase-3 (Tsamandas et al, 2003). Caspase-3, the main apoptotic executioner, causes chromatin condensation, protein breakdown, and DNA fragmentation (D'Amelio et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The mitochondrial outer membrane integrity is maintained by Bcl-2, while increased membrane permeability by Bax releases apoptogenic factors in the cytosol, which activate caspase-9 and caspase-3 (Tsamandas et al, 2003). Caspase-3, the main apoptotic executioner, causes chromatin condensation, protein breakdown, and DNA fragmentation (D'Amelio et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore changes of apoptosis and Bcl-2 family members should be studied according to the stages of disorder. Although the Bcl-2 expression has been investigated in different stages of some fibrotic diseases such as liver fibrosis (Tsamandas et al, 2003), unfortunately there is no study about the changes of Bcl-2 family proteins in various stages of pulmonary fibrosis to explore their correlation with the severity of this disease. More studies are needed in future to exactly clarify the importance of bcl-2 family in diagnosis, grading and treatment of pulmonary fibrosis.…”
Section: Perspectivementioning
confidence: 99%
“…Conflicting data have been reported to whether evolution of chronic liver disease towards cirrhosis is a consequence of increased apoptosis, reduced proliferation or a combination of both [15][16][17][18][19]. In HCV infection but also in primary biliary cirrhosis (PBC), both pro-and anti-apoptotic effects have been observed [20][21][22][23][24][25] and expression patterns may be different according to the stage of fibrosis progression [25]. We previously reported that Stat3 activity is disturbed in human end-stage ALD [26].…”
Section: Introductionmentioning
confidence: 98%